Regulatory specialization of xyloglucan (XG) and glucuronoarabinoxylan (GAX) in pericarp cell walls during fruit ripening in tomato (Solanum lycopersicum). - Ayami Takizawa; Hiromi Hyodo; Kanako Wada; Tadashi Ishii; Shinobu Satoh; Hiroaki Iwai (PLoS ONE)
Disassembly of cell wall polysaccharides by various cell wall hydrolases during fruit softening causes structural changes in hemicellulose and pectin that affect the physical properties and softening of tomato fruit. In a previous study, we showed that the changes in pectin during tomato fruit ripening were unique in each fruit tissue. In this study, to clarify the changes in hemicellulose in tissues during tomato fruit ripening, we focused on glucuronoarabinoxylan (GAX) and xyloglucan (XG). GAX was detected only in the skin and inner epidermis of the pericarp using LM11 antibodies, whereas a large increase in XG was detected in all fruit tissues using LM15 antibodies. The activity of hemicellulose degradation enzymes, such as β-xylosidase and α-arabinofuranosidase, decreased gradually during fruit ripening, although the tomato fruits continued to soften. In contrast, GAX and XG biosynthesis-related genes were expressed in all tomato fruit tissues even during ripening, indicating that XG was synthesized throughout the fruit and that GAX may be synthesized only in the vascular bundles and the inner epidermis. Our results suggest that changes in the cell wall architecture and tissue-specific distribution of XG and GAX might be required for the regulation of fruit softening and the maintenance of fruit shape.